Upaya Rehabilitas Ekosistem Pesisir Melalui Penanaman Mangrove di Selat Pedang, Desa Watubaing, Kecamatan Talibura - Fransiska Angelista Tati Boruk; Anicetus Ofansius Pedi; Carolina Laura Manis; Yosef Alfred Fandebrito; Fransiska Delfiana Urong; Maria Levita; Alfredo Marsis Dalo Soba (Bengkulu Institute, 2025)
Mangrove ecosystems play a crucial role in maintaining coastal stability, preventing abrasion, sequestering carbon, and providing habitats for various marine organisms. However, mangrove conditions in several coastal areas of Indonesia have been degraded due to human activities and natural factors. Watubaing Village, Talibura District, Sikka Regency is one of the areas with a high level of coastal abrasion, particularly in the Selat Pedang region. To address this issue, students of the Community Service Program (Kuliah Kerja Nyata or KKN) from Nusa Nipa University (Unipa) conducted a mangrove planting program. The methods included site surveys, community outreach, planting of Rhizophora sp. mangrove seedlings, and initial post-planting monitoring. A total of 30 seedlings were planted in an intertidal area of approximately 0.5 hectares, with an initial survival rate of about 95%. The activity involved around 50 participants, including students, local government, fishermen groups, and school students. The results indicated that the mangrove planting not only has the potential to reduce coastal abrasion but also enhances community awareness and participation in coastal conservation. Therefore, this KKN program serves as a tangible effort for ecosystem rehabilitation as well as an environmental education platform in Watubaing Village.